Behavioural weight loss treatment preferences of college students with overweight and obesity. Issue 1 (15th October 2019) - Bihuniak, Jessica D.; Bryant, Tiffany; Kleiman, Jennifer; Rotondo, Megan; Decoteau, Jessica; Haisley, Samantha; Monserrate, David; Cunningham, Michael; MacKenzie, Allison; Dauz, Steve; Ippolito, Rosann; Fernandes, Nicolle; et al.
Summary: The college environment increases risk of weight gain in young adults with overweight/obesity. Behavioural weight loss interventions are proven effective, however, young adults' adherence to such programs is poor. The purpose of the study was to determine weight loss treatment preferences of 2‐ and 4‐year college students for the development of population‐specific interventions. Students with a BMI ≥25, between 18 and 24 years of age, and enrolled in one of four institutions were recruited. A questionnaire was developed to assess students' preferences and was administered via Qualtrics. BMI was calculated from objectively assessed height and weight measurements. Descriptive analyses, chi‐square, Fisher's Exact Test, Mann‐Whitney U test and Cramer's V were performed. Participants (n = 133, age = 20.2 ± 1.8) predominately identified as female (70%), non‐Hispanic (68%) and Black/African American (32%) or White (32%). Fifty‐five percent met criteria for obesity. Most students preferred session length of ≤1 hour (78%), for meetings to be held on a weekday (70%) and for both a peer and a professional to co‐facilitate meetings (61%). Preferences for health outcomes and physical activity monitoring, type of physical activity, frequency of dietary monitoring, physical activity tracking method and interest in financial incentives to promote core treatment components differed between institutions. Heterogeneity in program preferences by college environment should be considered when designing weight loss interventions.